3x^2 + 5y^2+ 10z^2 -4xy -6yz +2 = 0
x^2 + 3y^2 -2xy -10y -2x + 20
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(E=-16x^2+3x-3=-\left(4x-\frac{3}{8}\right)^2-\frac{183}{64}\le\frac{-183}{64}\)
Vậy \(MaxE=\frac{-183}{64}\) khi \(x=\frac{3}{32}\)
Bạn xem lại đề phần \(F\) nhé.
\(G=-3x^2-9x+2=-3\left(x^2+3x-\frac{2}{3}\right)=-3[x^2+2x.\frac{3}{2}+\left(\frac{3}{2}\right)^2]+\frac{35}{4}\)
\(=-3\left(x+\frac{3}{2}\right)^2+\frac{35}{4}\le\frac{35}{4}\forall x\)
Vậy \(MaxG=\frac{35}{4}\) khi: \(\left(x+\frac{3}{2}\right)^2=0\Rightarrow x=\frac{-3}{2}\)
\(H=-7x^2+14x-3=-7\left(x^2-2x+\frac{3}{7}\right)=-7\left(x^2-2x+1\right)+4=-7\left(x-1\right)^2+4\le4\forall x\)
Vậy \(MaxH=4\) khi: \(\left(x-1\right)^2=0\Rightarrow x=1\)